Penguatan Social Support Orang Tua melalui Psikoedukasi pada Siswa SMP IT Madinah Al Fatih Gadur Kabupaten Padang Pariaman - Karima, Raisa; Oktari, Siska; Rozi Sastra Purna,; Dwi Puspasari,; Nelia Afriyeni,; Nisa Indah Pertiwi,; Puji Gufron Rhodes,; Istazro Rosyid Yurisman,; Karina Putri Iskandar,; Asla Al Mutmainnah, (Jurnal Pengabdian UNDIKMA, 2026)
This community service activity aims to assess the level of parental social support and to provide psychoeducation to parents and guardians of ninth-grade students at Madinah Al Fatih Gadur Islamic Junior High School, with the goal of enhancing their understanding of how to support their children's education and career planning. The program is implemented through face-to-face psychoeducational sessions, followed by small group discussions facilitated by a psychologist, involving a total of 49 parents and guardians. Data are collected using a Likert-scale questionnaire measuring four dimensions of social support: emotional, appraisal, instrumental, and informational support. Descriptive analysis reveals that 71.43% of respondents are categorized as having a moderate level of social support, while 14.29% fall into both the high and low categories. Emotional support demonstrates the highest mean score (M = 22.16), whereas instrumental support shows the lowest (M = 5.86), indicating that emotional support is more dominant than tangible assistance. These findings underscore the importance of strengthening parental roles in supporting children's educational achievement and facilitating early career planning through the provision of optimal social support.